Profiles of Patients with Low Back Pain Caused by Disc Herniation in the Neurology Outpatient Clinic of Dr. Soetomo General Academic Hospital Surabaya during the Period of 2021 - Agindra, Bani; Hidayati, Hanik Badriyah; Widhiyanto, Lukas; Herawati, Lilik (AKSONA, 2024)
Highlight: The degenerative process plays a dual role, both protecting from and causing disc herniation. Men have a quicker degeneration rate at a younger age, while women have a quicker rate at an older age. Occupational factors such as physical workload, repetition, bending, and sitting periods all contribute to disc herniation.   ABSTRACT Introduction: Low back pain (LBP) refers to a sensation of pain or discomfort occurring in the region between the lowest costal and gluteal crease, with or without leg pain. Damage to the annulus fibrosus causes disc herniation, allowing the nucleus pulposus to herniate into the spinal canal. In less than 5% of cases, LBP is caused by disc herniation. Objective: This study examined the profiles of individuals with herniated LBP discs and related factors at Dr. Soetomo General Academic Hospital Surabaya. Methods: The study was conducted at Dr. Soetomo General Academic Hospital Surabaya using secondary data from medical records, which was then analyzed using descriptive statistics. Results: Fifty-eight LBP patients with herniated discs were enrolled in this study. The patient sample ranged from 23 to 74 years old, with a mean of 47,98±14,92. The majority of patients (29.3%) were 31–40 years old. Male and female prevalence rates were the same. Employees have the highest percentage of any occupation group, with 56.9%. Conclusion: Some of the findings clarify previous studies. Age, gender, and occupation were all linked to the occurrence of either LBP or disc herniation. However, our data cannot indicate whether or not these factors contribute to the occurrence of LBP and disc herniation. Therefore, more research is required to understand these factors and their relation to disc herniation and LBP.